Recovery of Belida Fish Bone Byproduct as a Rich Calcium Powder by Alcali Method - Indriati Kusumaningrum; Doddy Sutono; Bagus Fajar Pamungkas (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
Belida (Chitala sp.) bone is one of the waste from amplang processing which not treated properlyyet until now especially in East Kalimantan. One type of the usage of this waste is processed to fish bonepowder as calcium source. The aim of this study was to determine the best treatment (boiling frequency)to produce belida fish bone powder which the best characteristics based on highest calcium content. Theprocessing applied alkali method (used NaOH) to produce belida fish bone powder. The treatment of thisstudy was boiling frequency, i.e. P1 (once boiling), P2 (twice boiling), P3 (three times boiling), and P4 (fourtimes boiling) with 30 minutes on each boiling. Observed parameters in this study were moisture content,ash content, protein content, fat content, calcium content, phosphor content, pH and whiteness. The resultsshowed that four times boiling gave the best result with the highest calcium content 31.31%. The range ofcalcium content was 28.25%-31.31%. While the range of phosphor content was 3.95%-4.06%.